Freedom to Evangelize vs Freedom to Seek Justice? - Taber, Charles R. (Transformation, 1991)
Contrary to popular imagination, the division between those countries which allow freedom to preach the gospel and those which deny it is not the line between Marxist and non-Marxist states. Both left and right wing authoritarian regimes tolerate gospels that focus exclusively on individual religious concerns that are politically uncritical. This frees them from any criticism on religious grounds. There is another formulation of the gospel which is not reductionist and which asserts the Lordship of Christ over the entire universe and all aspects of its life. Such a formulation is a serious threat to any totalitarian regime of whatever ideology.